(( he effect of the Joyce and Will model on the acquisition ‎of grammatical concepts for second-grade intermediate ‎students))‎‏ ‏ (Journal of the College of Basic Education, 2022)
The aim of the research is to (the effect of the Joyce and Will model on the acquisition of grammatical concepts for second-grade students) to achieve the goal of the research. Al-Erada Intermediate School for Girls. The research sample consisted of (74) female students, and it was distributed to two groups of them, the group The experimental group consisted of (36) female students who studied grammatical concepts according to a model. Joyce and Will, and the control group consisted of 38 (students who studied grammatical concepts according to the usual method, and the process of equivalence between the two groups was conducted n the subject of Arabic grammar for the first semester, and the academic achievement of the parents, then the researcher preparedThe teaching plans for the subjects included in the experiment showed that the result was superior to the Joyce and Will modelOn the usual method, according to the results reached by the researcher, she recommended an emphasis on the use of modern teaching models in teaching. ?As an extension of this research, the researcher suggested conducting similar studies to the current study in other stages and classes in the branches of the Arabic language: criticism, literature, morphology and others